Characterization and Classification of the Mawer Forest Soils of Lesser Himalayas of North Kashmir - S.A. Bangroo (Journal of the Indian Society of Soil Science, 2022)
Soil is an important component of the forest ecosystem. The inventory and assessment of the forest soil resource provide critical baseline information on forest health and productivity. Therefore, a study for the characterization and classification of the soils of Mawer forest range of North Kashmir Himalayas was conducted. In this study, twelve representative soil profiles along with two altitude gradients on Northern and Southern aspects of Mawer forest range were evaluated for soil characterization and classification. The soils show varying degree of profile development varying from A-B to A-C type with the well-developed sub-surface argillic horizon (Bt) on moderately steep slopes and cambic horizon on steep slopes. The soils are silty loam to loam in texture, slightly acidic to alkaline (pH 5.5 to 6.8) in reaction, non-saline (EC 0.02 to 0.14 dS m-1) with higher organic carbon content on north-facing profiles. Available nutrients are higher on the northern aspect of surface horizons with higher calcium and potassium content on higher altitudes and magnesium and sodium content on lower altitudes. As per soil classification, major soils belong to Udothents and Haploudolls followed by Hapludalfs, Agriudolls, and Eutrochrepts at a great group level.